Music-based interventions for adolescent depression and anxiety: a critical narrative review - Li, Xin-Rui; Zhong, Bao-Liang (AME Medical Journal, 2026)
Background and Objective: Adolescence represents a critical developmental window marked by a rising prevalence of anxiety and depression, yet treatment engagement remains persistently low. Music-based interventions have emerged as a promising therapeutic modality, uniquely aligned with adolescent cultural norms and capable of overcoming barriers to traditional psychotherapy. This critical narrative review aims to synthesize theoretical mechanisms and empirical evidence while critically examining methodological limitations and outcome heterogeneity in music interventions for adolescent depression and anxiety.Methods: A critical narrative review was conducted across PubMed, PsycINFO, Web of Science, and Scopus (January 2015–August 2025), synthesizing 63 original English-language studies examining music-based interventions targeting adolescent depression and anxiety.Key Content and Findings: While music interventions engage neurobiological, physiological, and psychosocial pathways, efficacy varies considerably. Active interventions generally yield stronger short-term improvements than receptive approaches. However, evidence is constrained by methodological heterogeneity, inconsistent intervention protocols, and limited long-term follow-up. Negative or non-significant findings are underreported, and effects for severe depression remain unestablished.Conclusions: Music-based interventions show promise as complementary approaches for mild-to-moderate adolescent depression and anxiety, but cannot replace evidence-based pharmacotherapy or psychotherapy for severe presentations. Critical limitations—including protocol variability, outcome measurement inconsistency, and lack of mechanistic specificity—preclude definitive efficacy claims. Future research requires standardized protocols, disaggregated outcome reporting, and rigorous long-term trials.